The analysis of the quality of red fermented rice (RFR) product with Monascus purpureus 3090 - DJUMHAWAN R. PERMANA; SUNNATI MARZUKI; D. TISNADJAJA (Society for Indonesian Biodiversity, 2004)
Analysis of red fermented rice product with Monascus purpureus 3090 was conducted on monascus floor product (MFP- 264), MFP-244 and rice monascus product (RMP). Evaluation of microbiological, pigment intensity and lovastatine contentanalysis result was aimed to see quality differences on each production of 5 kg rice raw material. Of both product types(MFP-264, RMP) which only oven dried compare to MFP-244 which is sterilized in autoclave showed a significantly difference of population level on total microorganism colonies, that is mould 26x106 propagule/ml, bacteria 13x106 cell/ml(MFP-264), mould 85x106 propagule/ml, bacteria 265x106 cell/ml (RMP). The MFP-244 produced highest absorptionspectra 0.3513-0.4050 compare to MFP-264 0.3110-0.3324, rice monascus product (RMP) 0.3343-0.3663. Pigment biosynthesis seems occurred at sexual developmental stage or conidia formation of M. purpureus 3090, which is produced color changes of yellow pigment, orange pigment, and red pigment. Lovastatine content of MFP-264 has Rf value 0.84 MFP-244 Rf 0.83 and RMP Rf 0.82 showed higher value compare to Rf 0.81 of the lovastatine standard solution.ïƒ“ 2004 Jurusan Biologi FMIPA UNS SurakartaKey words: quality analysis, rice fermented product, Monascus purpureus 3090